Preparation and use method of silicification treatment agent
By using silicification treatment agents prepared by materials such as modified graphene and nanoceramic powder, combined with alkaline cleaning, open flame high-temperature burning and vacuum coating technology, a silicified ceramic film layer is formed, which solves the problems of insufficient coating bonding, salt spray resistance and corrosion resistance of metal parts in the prior art, and achieves higher performance and longer service life.
Patent Information
- Application Number
- CN202510174855.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-18
AI Technical Summary
Existing metal anti-corrosion technology is difficult to effectively improve the coating bonding, salt spray resistance and corrosion resistance of metal components.
A silicification treatment agent is adopted, including modified graphene, sheet-like inorganic minerals, nanoceramic powder, acrylate polymer emulsion, dispersant and defoaming agent, and a silicified ceramic film layer closely bonded to the metal substrate through alkaline cleaning, open flame high-temperature burning and vacuum coating.
It significantly improves the coating bonding, salt spray resistance and corrosion resistance of metal parts, extends the service life of metal parts and reduces maintenance costs.
Smart Images

Figure CN119639291A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal anticorrosion, and in particular relates to a preparation and use method of a siliconizing treatment agent. Background Art
[0002] In the natural environment or during use, metals will gradually be damaged due to chemical reactions such as oxidation and corrosion, resulting in performance degradation or even failure. Through effective anti-corrosion measures, the corrosion rate of metals can be significantly slowed down, thereby extending their service life and reducing the replacement or maintenance costs caused by corrosion. Metal anti-corrosion is of great significance in ensuring safety, improving economic benefits, protecting the environment and promoting technological progress.
[0003] Commonly used metal anti-corrosion methods include coating protection, electrochemical protection, corrosion inhibitor protection, surface treatment protection, etc. Among them, coating protection effectively isolates the metal from direct contact with the corrosive medium by applying one or more layers of anti-corrosion coating on the metal surface, thereby achieving the purpose of anti-corrosion. This method has the advantages of low cost, convenient construction, and significant effect. It is suitable for various metal materials and different use environments. It is currently the most widely used metal anti-corrosion method. Before painting metal parts, the metal is often pre-treated by phosphating, chromating, ceramic treatment, silane treatment, etc. to improve the metal's corrosion resistance and coating adhesion. In recent years, emerging metal pre-treatment technologies such as silicified metal ceramic film technology and self-assembled film technology have been widely used in the pre-treatment of various metal materials such as steel, aluminum, and copper due to their environmental protection, energy saving, high efficiency, no need for water washing, and strong adaptability to metal substrates. Among them, siliconized metal ceramic film technology was initially used in the aerospace field, mainly used to improve the corrosion resistance and coating adhesion of metal parts. In recent years, with the continuous development of technology, silicon ceramic film technology has gradually been applied to civil fields such as automobiles, ships, and construction. At present, silicon ceramic film technology has become one of the important technologies in the field of coating pretreatment, and is expected to be applied and promoted in more fields in the future.
[0004] In order to adapt to market demand and keep up with the development of cutting-edge technologies, it is an important task for technical personnel in this field to develop high-performance siliconizing agents and apply them to the pretreatment of metal materials, improve the surface structure and performance of metal parts, and improve the coating adhesion, salt spray resistance, and corrosion resistance of metal parts. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing and using a siliconizing agent to improve the surface structure and performance of metal parts, and to enhance the coating bonding strength, salt spray resistance, corrosion resistance and other properties of the metal parts.
[0006] In view of this, the present invention provides a method for preparing a siliconizing agent, wherein the siliconizing agent comprises the following raw materials in parts by weight: 5-10 parts of modified graphene; 3-5 parts of flaky inorganic minerals; 15-30 parts of nano ceramic powder; 80-130 parts of acrylic polymer emulsion; Dispersant 0.5~3 parts; Defoaming agent 0.3~1 part.
[0007] Furthermore, the preparation process of the modified graphene is as follows: First, 5 to 10 parts by weight of graphene microsheets are dispersed in 80 to 150 parts by weight of an ethanol aqueous solution, wherein the ethanol content in the ethanol aqueous solution is 40 to 50 wt%, then an acid solution is added dropwise to adjust the pH of the mixed solution to 2.5 to 4, and then 50 to 70 parts by weight of an ethyl orthosilicate solution is slowly added dropwise, wherein the ethyl orthosilicate solution is an ethanol solution with an ethyl orthosilicate content of 10 to 20 wt%; after the ethyl orthosilicate solution is added dropwise, the reaction is continued with stirring for 3 to 5 hours, and then filtered, and the obtained solid powder is calcined at 500 to 600° C. for 1 to 2 hours under the protection of an inert atmosphere to obtain a flaky graphene with silicon dioxide deposited on the surface; The obtained flaky graphene with surface-deposited silicon dioxide is then dispersed in 5-10 parts by weight of polydimethylsilicone oil and 3-5 parts by weight of linear aminosilicone oil. After the graphene microsheets are evenly dispersed by ultrasound, the obtained mixed system is put into a reactor, the temperature is raised to 300-400° C. under vacuum, and the temperature is kept for reaction for 2-3 hours, then the temperature is lowered to 80-120° C., 3-5 parts by weight of linear hydroxyl silicone oil are added, and the reaction is carried out for 1-2 hours under stirring to obtain modified graphene.
[0008] Furthermore, the flaky inorganic mineral is selected from one or more of mica, kaolin, talc, montmorillonite, chlorite, and pyrophyllite, and the average thickness of the flaky inorganic mineral is ≤1 um, and the particle size is ≤10 um.
[0009] Furthermore, the monomers forming the acrylic ester polymer include 40 to 60 parts by weight of methyl methacrylate, 15 to 20 parts by weight of n-butyl acrylate, 5 to 10 parts by weight of pentaerythritol triacrylate, and 5 to 10 parts by weight of ethyl acrylate.
[0010] Furthermore, the preparation process of the acrylic polymer emulsion is as follows: First, a certain amount of emulsifier is added to deionized water to prepare solution 1 with an emulsifier content of 3-5wt%, and a certain amount of potassium persulfate is added to deionized water to prepare solution 2 with a potassium persulfate content of 0.5-3wt%. Then, methyl methacrylate, n-butyl acrylate, pentaerythritol triacrylate and ethyl acrylate are added to solution 1, and after stirring evenly, the obtained mixed solution is heated to 70-80°C, and solution 2 is added, and then the reaction is stirred at 70-80°C for 1-2h, and then a photoinitiator is added, and after stirring to make the mixture evenly mixed, the acrylic ester polymer emulsion is obtained.
[0011] Furthermore, in the preparation process of the acrylic polymer emulsion, the weight ratio of the monomer, emulsifier and photoinitiator added to form the acrylic polymer is (100-150): (3-8): (1-5).
[0012] Furthermore, the preparation method of the siliconizing agent comprises: First, 3 to 5 parts by weight of a flaky inorganic mineral and 5 to 10 parts by weight of deionized water are mixed, stirred evenly, and allowed to stand for 5 to 10 minutes, and then an appropriate amount of deionized water is added to prepare a suspension having a flaky inorganic mineral content of 1 to 3 wt%, and then 15 to 30 parts by weight of a nano-ceramic powder is added to the suspension of the flaky inorganic mineral, and stirred at a speed of 300 to 1000 rpm for 5 to 10 minutes, and then the obtained mixed solution is filtered, and the powder obtained by filtration is placed in a vacuum oven at 30 to 50° C. and dried to constant weight, and the obtained mixture is set aside; The modified graphene, dispersant and defoamer in the formula amount are added to the acrylic polymer emulsion, stirred to make the mixture uniform, and then a mixture of nano-ceramic powder and flaky inorganic minerals is added, and after shearing and dispersion, the siliconization treatment agent is obtained.
[0013] A method for using a siliconizing agent, the method for using the siliconizing agent is used for the above-mentioned siliconizing agent, and the method for using the siliconizing agent comprises the steps of: S1, using alkaline cleaning liquid to clean the metal surface; S2, roughening the metal surface by high temperature burning with open flame; S3, applying the siliconizing agent.
[0014] Furthermore, the step S2 includes: placing the metal component in an open flame at 600-800° C. for high-temperature burning, and the high-temperature burning treatment time is 3-10 minutes.
[0015] Furthermore, in step S3, the process of applying the siliconizing agent is as follows: First, place the metal parts in a sealed container and fill it with the siliconizing agent. After the metal parts are completely immersed in the siliconizing agent, evacuate the sealed container to a pressure of 10-50 kPa and maintain the pressure for 5-10 minutes. Then, inject air into the sealed container. When the pressure in the sealed container reaches atmospheric pressure, open the sealed container, take out the metal parts, and then place the metal parts in an oven at 60-80°C for drying.
[0016] The beneficial effects of the present invention are: The siliconizing agent of the present invention can improve the coating bonding strength, salt spray resistance, corrosion resistance and other properties of metal parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the coating structure formed after the siliconizing agent of the present invention is applied to the metal surface; The symbols in the figure are: 1-metal substrate, 2-nanoscale micropores, 3-siliconized ceramic membrane layer. DETAILED DESCRIPTION
[0018] The following will be combined with the drawings in the embodiments of the present application to clearly describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments in the present application belong to the scope of protection of this application.
[0019] In the description of this application, it should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to this application. For ease of description, the techniques, methods and devices known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, the techniques, methods and devices should be considered as part of the authorization specification.
[0020] It should be noted that, in the present application, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises one..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be noted that the scope of the method and device in the embodiment of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0021] A method for preparing a siliconizing agent, wherein the siliconizing agent comprises the following raw materials in parts by weight: 5-10 parts of modified graphene; 3-5 parts of flaky inorganic minerals; 15-30 parts of nano ceramic powder; 80-130 parts of acrylic polymer emulsion; Dispersant 0.5~3 parts; Defoaming agent 0.3~1 part.
[0022] Furthermore, the preparation process of the modified graphene is as follows: First, 5 to 10 parts by weight of graphene microsheets are dispersed in 80 to 150 parts by weight of an ethanol aqueous solution, wherein the ethanol content in the ethanol aqueous solution is 40 to 50 wt%, then an acid solution is added dropwise to adjust the pH of the mixed solution to 2.5 to 4, and then 50 to 70 parts by weight of an ethyl orthosilicate solution is slowly added dropwise, wherein the ethyl orthosilicate solution is an ethanol solution with an ethyl orthosilicate content of 10 to 20 wt%; after the ethyl orthosilicate solution is added dropwise, the reaction is continued with stirring for 3 to 5 hours, and then filtered, and the obtained solid powder is calcined at 500 to 600° C. for 1 to 2 hours under the protection of an inert atmosphere to obtain a flaky graphene with silicon dioxide deposited on the surface; The obtained flaky graphene with surface-deposited silicon dioxide is then dispersed in 5-10 parts by weight of polydimethylsilicone oil and 3-5 parts by weight of linear aminosilicone oil. After the graphene microsheets are evenly dispersed by ultrasound, the obtained mixed system is put into a reactor, the temperature is raised to 300-400° C. under vacuum, and the temperature is kept for reaction for 2-3 hours, then the temperature is lowered to 80-120° C., 3-5 parts by weight of linear hydroxyl silicone oil are added, and the reaction is carried out for 1-2 hours under stirring to obtain modified graphene.
[0023] Preferably, the tetraethyl orthosilicate solution needs to be added dropwise within 60 to 90 minutes.
[0024] Preferably, the particle size of the graphene microsheets is 10-50 um.
[0025] In the preparation process of the modified graphene, firstly, ethyl orthosilicate is hydrolyzed to form silicon dioxide precipitate particles on the surface of graphene microsheets, and the silicon dioxide particles are more tightly bound through a subsequent high-temperature calcination process, so that a more stable and dense deposition layer can be formed on the graphene surface; at the same time, the high-temperature calcination can remove moisture and solvent on the graphene surface, promote the chemical bonding between silicon dioxide and graphene, make the silicon dioxide deposition layer more firmly attached to the graphene surface, optimize the interface between silicon dioxide and graphene, reduce interface defects, reduce pores and defects on the graphene surface, and improve the density and mechanical strength of the silicon dioxide deposition layer.
[0026] In the present invention, the formation of silica precipitate particles can improve the surface properties of graphene microsheets. The silica layer, as an intermediate layer, can form silicon-oxygen bonds on the surface of graphene microsheets, which can enhance the compatibility between graphene and other components, thereby improving the dispersion performance, compatibility and interface bonding force of graphene microsheets; at the same time, the silica precipitate particles can also improve the surface structure of graphene microsheets, forming an uneven microstructure on its surface, further improving the anti-agglomeration ability of graphene microsheets and the ability to combine with other components in the siliconization treatment agent. At the same time, the silica deposition layer can also shield the conductivity of graphene, inhibit its "cathode corrosion promotion activity", enhance the barrier effect of graphene, make it more difficult for corrosive media to penetrate the coating, and improve the "passive protection" ability of the coating.
[0027] On this basis, by dispersing flaky graphene in polydimethylsilicone oil and linear aminosilicone oil, after high temperature treatment at 300-400°C, polydimethylsilicone oil and linear aminosilicone oil undergo high temperature cracking, and the long chain structure thereof is cracked into short chain siloxane, thereby exposing a large number of active groups, such as hydroxyl, alkoxy, amino, etc. These active groups have extremely high reactivity and are attached to the surface of graphene, which can increase the number of active groups on the surface of graphene, further improve the dispersibility, compatibility and interfacial bonding force of graphene, and facilitate the combination and cross-linking of graphene with other components in the siliconizing agent during the film forming process, increase the cross-linking density and integrity, and improve the strength of the formed siliconized ceramic film layer. Since graphene is an inorganic substance and cannot directly form a chemical bond with an organosilicon material, in the present invention, by using silicone oil to modify the flaky graphene with silicon dioxide deposited on the surface, the bonding ability between graphene and the organosilicon material can be improved.
[0028] Furthermore, by adding linear hydroxy silicone oil, since the linear segments of the linear hydroxy silicone oil carry reactive groups such as hydroxyl groups, they can combine with the active groups on the graphene surface or the amino groups, carboxyl groups, etc. in the acrylic polymer, etc. to form a network structure, further improving the compatibility and interfacial bonding strength of the graphene. In this way, by using silicone oil, the pores and defects inside the film layer caused by the introduction of inorganic particles such as graphene and silica particles in the silicified ceramic film layer can be improved, and the anti-corrosion performance of the film layer can be improved.
[0029] In addition, linear hydroxy silicone oil is a kind of organic silicon compound containing hydroxyl groups. The silicon oxygen chain and hydroxyl groups in its molecular structure give it unique surface activity. The addition of linear hydroxy silicone oil can adjust the surface tension of the siliconizing agent, making it easier for the agent to spread on the surface of the substrate, improving the adhesion, leveling and hydrophobicity of the siliconizing agent, making the coating more uniform and smooth, and preventing water penetration. At the same time, the methyl group in the linear hydroxy silicone oil is hydrophobic, which can improve the hydrophobicity of the formed siliconized ceramic film layer 3.
[0030] As some examples of the present invention, the flaky inorganic mineral is selected from one or more of mica, kaolin, talc, montmorillonite, chlorite, pyrophyllite and the like.
[0031] Preferably, the average thickness of the flaky inorganic mineral is ≤1 um, and the particle size is ≤10 um.
[0032] In the present invention, by using modified graphene and flaky inorganic minerals in combination, a maze-like shielding structure can be formed in the film layer by staggered arrangement of modified graphene and flaky inorganic minerals, thereby effectively inhibiting the infiltration, penetration and diffusion of corrosive media, and improving the phenomenon in existing coatings where the current reaction in the film layer accelerates metal corrosion due to the introduction of graphene.
[0033] As some examples of the present invention, the acrylic ester polymer is a polymer formed by polymerizing one or more monomers selected from methyl methacrylate, ethyl acrylate, n-butyl acrylate, butyl methacrylate, pentaerythritol triacrylate, isooctyl acrylate, and the like.
[0034] Preferably, the monomers forming the acrylic ester polymer include 40-60 parts by weight of methyl methacrylate, 15-20 parts by weight of n-butyl acrylate, 5-10 parts by weight of pentaerythritol triacrylate, and 5-10 parts by weight of ethyl acrylate.
[0035] In the present invention, the monomers forming the acrylic polymer include multiple monomers, among which methyl methacrylate can be used as a hard monomer to provide a higher hardness for the film layer formed by coating, n-butyl acrylate can be used as a monomer with medium hardness, and ethyl acrylate can be used as a soft monomer, which is compounded with the methyl methacrylate to form a film layer with higher strength and toughness, so that it can provide good barrier protection for metals and is not easy to crack. The addition of pentaerythritol triacrylate enables the acrylic polymer to be further cross-linked and polymerized on the surface of the metal substrate 1 under the action of a photoinitiator after coating, and solidified to form a stable silicified ceramic film layer 3, thereby improving the mechanical strength and density of the silicified ceramic film layer 3.
[0036] Furthermore, the preparation process of the acrylic polymer emulsion is as follows: First, a certain amount of emulsifier is added to deionized water to prepare solution 1 with an emulsifier content of 3-5wt%, and a certain amount of potassium persulfate is added to deionized water to prepare solution 2 with a potassium persulfate content of 0.5-3wt%. Then, a formulated amount of methyl methacrylate, n-butyl acrylate, pentaerythritol triacrylate and ethyl acrylate are added to solution 1, and after stirring evenly, the obtained mixed solution is heated to 70-80°C, and solution 2 is added, and then the reaction is stirred at 70-80°C for 1-2h, and a photoinitiator LAP (i.e., phenyl (2,4,6 trimethylbenzoyl) lithium phosphate) is added, and after stirring to make the mixture evenly mixed, the acrylic ester polymer emulsion is obtained.
[0037] As some examples of the present invention, the emulsifier is sodium dodecylbenzene sulfonate.
[0038] Preferably, during the preparation of the acrylic polymer emulsion, the weight ratio of the monomer, emulsifier and photoinitiator added to form the acrylic polymer is (100-150): (3-8): (1-5).
[0039] As some examples of the present invention, the dispersant is selected from sulfonate dispersants, carboxylate dispersants, polyvinyl alcohol and the like.
[0040] As some examples of the present invention, the defoaming agent is selected from polycarboxylate defoaming agents, silicone defoaming agents, and the like.
[0041] Furthermore, the preparation method of the siliconizing agent comprises: First, 3 to 5 parts by weight of a flaky inorganic mineral and 5 to 10 parts by weight of deionized water are mixed, stirred evenly, and allowed to stand for 5 to 10 minutes, and then an appropriate amount of deionized water is added to prepare a suspension having a flaky inorganic mineral content of 1 to 3 wt%, and then 15 to 30 parts by weight of a nano-ceramic powder is added to the suspension of the flaky inorganic mineral, and stirred at a speed of 300 to 1000 rpm for 5 to 10 minutes, and then the obtained mixed solution is filtered, and the powder obtained by filtration is placed in a vacuum oven at 30 to 50° C. and dried to constant weight, and the obtained mixture is set aside; The modified graphene, dispersant and defoamer in the formula amount are added to the acrylic polymer emulsion, stirred to make the mixture uniform, and then a mixture of nano-ceramic powder and flaky inorganic minerals is added, and after shearing and dispersion, the siliconization treatment agent is obtained.
[0042] In the preparation process of the siliconizing agent, the flaky inorganic mineral with good hydrophilicity is firstly moistened with water, and then further prepared into a suspension of the flaky inorganic mineral. On this basis, the adsorption effect between the nano-ceramic powder and the flaky inorganic mineral is utilized to obtain the flaky inorganic mineral with the nano-ceramic powder adsorbed on the surface. In this way, while achieving good dispersion and adsorption of the flaky inorganic mineral and the nano-ceramic powder, the agglomeration of the flaky inorganic mineral can be improved.
[0043] Furthermore, in the subsequent drying process, the water is quickly dried out through vacuum drying technology, which not only shortens the drying time but also prevents the agglomeration of flaky inorganic minerals.
[0044] In addition, the present invention also provides a method for using the above-mentioned siliconizing agent, which comprises the steps of: S1, using alkaline cleaning liquid to clean the metal surface; S2, roughening the metal surface by high temperature burning with open flame; S3, applying the siliconizing agent.
[0045] Specifically, the step S1 includes: First, use alkaline cleaning solution to clean the metal surface, then rinse the alkaline cleaning solution with clean water and dry it.
[0046] Preferably, the alkaline cleaning solution includes 5-10wt% of sodium carbonate, 0.5-1wt% of an emulsifier (such as OP-10, AES, AEO-3, AEO-7, AEO-9, etc.), 10-20wt% of sodium phosphate and 10-20wt% of sodium silicate, i.e., sodium silicate.
[0047] Furthermore, the step S2 comprises: The metal parts are placed in an open flame at 600~800℃ for high-temperature burning, and the high-temperature burning treatment time is 3~10 minutes.
[0048] As some examples of the present invention, the high-temperature burning flame is a flame generated by the combustion of combustible gases such as hydrogen, alcohol, liquefied petroleum gas, natural gas, biogas, water gas, and petroleum gas.
[0049] As some examples of the present invention, for larger metal parts, during the high-temperature burning process, the flame cannot fully cover the surface of the metal parts. At this time, it is necessary to continuously move the flame to treat different areas of the metal parts. The cumulative time that the area that needs to be roughened is burned by the open flame should be no less than 3 minutes.
[0050] In the high-temperature burning process, since the flame generated by the combustible gas contains reducing gases such as carbon monoxide and hydrogen, and the air also contains gases such as oxygen, under the action of the high-temperature flame and atmosphere formed by the combustible gas, a reaction area can be formed on the surface of the metal part by utilizing the high temperature of the gas, and violent gas molecule and atom diffusion and oxidation-reduction reaction occur on the metal surface in the reaction area, wherein chemical reactions occur between the gas molecules infiltrated into the lattice inside the metal part to generate large-volume, volatile gases such as CO2 and water, accompanied by the aggregation and expansion of these volatile gases inside the metal. When the content of these volatile gases inside the metal exceeds its solubility, these volatile gases will overflow from the inside of the metal, and then form nanoscale pores with a diameter of 10~1000nm on the metal surface. These nanoscale pores can not only change the microstructure of the metal surface, but also improve the roughness of the metal surface through the dispersed nanoscale pores, thereby improving its ability to combine with the silicided ceramic film layer 3. At the same time, during the high-temperature burning process, the surface of the metal parts may also produce slight oxidation. The oxide layer formed by oxidation of some metals, such as aluminum and chromium, is very dense and stable, which can effectively isolate the metal matrix from the contact with the corrosive medium, thereby significantly improving the corrosion resistance of the metal. However, for some metals, such as iron, the oxide layer formed after oxidation is relatively loose and easy to fall off. It is necessary to pay attention to improving the adverse effects of the oxide layer by changing the ratio of oxidizing and reducing gases generated in the combustible gas or introducing reducing gases such as hydrogen after the burning treatment for reduction.
[0051] As some examples of the present invention, the roughening treatment of the metal surface by high-temperature burning with an open flame in the present invention can be performed on all surfaces of the metal parts, and can also be adjusted as needed, such as only the edges, sharp corners, and parts of the metal parts immersed in specific media (such as seawater) where the film layer is weakly bonded to the metal substrate and easily fall off due to external forces can be treated, so as to locally strengthen the bonding force between the silicided ceramic film layer 3 and the metal substrate 1.
[0052] The nanoscale pores formed by the high-temperature calcination process in the present invention are pores generated in situ on the metal surface, and their thickness is extremely small, about nanometers, and are not easy to fall off. They can effectively improve the microstructure of the surface of the metal substrate 1 and enhance the bonding force between the surface of the metal substrate 1 and the silicided ceramic film layer 3.
[0053] Furthermore, in step S3, the process of applying the siliconizing agent is as follows: First, place the metal parts in a sealed container and fill it with the siliconizing agent. After the metal parts are completely immersed in the siliconizing agent, evacuate the sealed container to a pressure of 10-50 kPa and maintain the pressure for 5-10 minutes. Then, inject air into the sealed container. When the pressure in the sealed container reaches atmospheric pressure, open the sealed container, take out the metal parts, and then place the metal parts in an oven at 60-80°C for drying.
[0054] In the present invention, if Figure 1 As shown, after the metal surface is roughened by high-temperature burning with an open flame, nanoscale micropores 2 are formed on the surface of the metal substrate 1, and after vacuum coating, a silicided ceramic film layer 3 tightly bonded to the metal substrate 1 is obtained.
[0055] The siliconization treatment agent of the present invention is illustrated by specific embodiments below: Example 1 Preparation of modified graphene: First, 8 parts by weight of graphene microsheets are dispersed in 100 parts by weight of an ethanol aqueous solution, wherein the ethanol content in the ethanol aqueous solution is 40 wt%, then an acid solution is added dropwise to adjust the pH of the mixed solution to 3, and then 60 parts by weight of an ethyl orthosilicate solution is slowly added dropwise, wherein the ethyl orthosilicate solution is an ethanol solution with an ethyl orthosilicate content of 15 wt%, and the ethyl orthosilicate solution needs to be added dropwise within 60 minutes; after the ethyl orthosilicate solution is added dropwise, stirring is continued for 4 hours, and then filtered, and the obtained solid powder is calcined at 500° C. for 2 hours under the protection of an inert atmosphere to obtain a flaky graphene with silicon dioxide deposited on the surface; The obtained flaky graphene with surface-deposited silicon dioxide is then dispersed in 10 parts by weight of polydimethylsilicone oil and 3 parts by weight of linear aminosilicone oil. After the graphene microsheets are evenly dispersed by ultrasound, the obtained mixed system is put into a reactor, heated to 350°C under vacuum, kept warm for 2 hours, then cooled to 100°C, and 5 parts by weight of linear hydroxyl silicone oil are added. After reacting for 1 hour under stirring, modified graphene is obtained.
[0056] Example 2 Preparation of Acrylate Polymer Emulsion First, a certain amount of sodium dodecylbenzene sulfonate is added to deionized water to prepare solution 1 with a sodium dodecylbenzene sulfonate content of 3wt%, and a certain amount of potassium persulfate is added to deionized water to prepare solution 2 with a potassium persulfate content of 1wt%. Then, 50 parts by weight of methyl methacrylate, 15 parts by weight of n-butyl acrylate, 10 parts by weight of pentaerythritol triacrylate and 5 parts by weight of ethyl acrylate are added to solution 1, and after stirring evenly, the obtained mixed solution is heated to 70°C, and solution 2 is added, and then the reaction is stirred at 70°C for 1.5h, and then a photoinitiator LAP is added, and after stirring to make the mixture evenly mixed, the acrylate polymer emulsion is obtained, wherein the weight ratio of the added amount of the monomer, emulsifier and photoinitiator to form the acrylate polymer is 100:5:3.
[0057] Example 3 Preparation of siliconizing agent First, 3 parts by weight of a flaky inorganic mineral and 5 parts by weight of deionized water were mixed, stirred evenly, and allowed to stand for 10 minutes, and then an appropriate amount of deionized water was added to prepare a suspension having a flaky inorganic mineral content of 2 wt%, and then 15 parts by weight of a nano-ceramic powder was added to the suspension of the flaky inorganic mineral, and stirred at a speed of 300 rpm for 8 minutes, and then the obtained mixed solution was filtered, and the powder obtained by filtration was placed in a vacuum oven at 30° C. and dried to constant weight, and the obtained mixture was set aside; 5 parts by weight of the modified graphene prepared in the above embodiment 1, 0.5 parts by weight of a dispersant, and 0.3 parts by weight of a defoaming agent are added to 80 parts by weight of the acrylic polymer emulsion prepared in the above embodiment 2, and after stirring to make the mixture uniform, a mixture of nano-ceramic powder and flaky inorganic minerals is added, and after shearing and dispersion, the siliconization treatment agent is obtained.
[0058] Example 4 Preparation of siliconizing agent First, 4 parts by weight of a flaky inorganic mineral and 8 parts by weight of deionized water were mixed, stirred evenly, and allowed to stand for 5 minutes, and then an appropriate amount of deionized water was added to prepare a suspension having a flaky inorganic mineral content of 3 wt%, and then 20 parts by weight of nano-ceramic powder was added to the suspension of the flaky inorganic mineral, and stirred at a speed of 500 rpm for 5 minutes, and then the obtained mixed solution was filtered, and the powder obtained by filtration was placed in a vacuum oven at 40°C and dried to constant weight, and the obtained mixture was set aside; 8 parts by weight of the modified graphene prepared in the above embodiment 1, 1 part by weight of a dispersant, and 0.6 parts by weight of a defoaming agent are added to 100 parts by weight of the acrylic polymer emulsion prepared in the above embodiment 2, and after stirring to make the mixture uniform, a mixture of nano-ceramic powder and flaky inorganic minerals is added, and after shearing and dispersion, the siliconization treatment agent is obtained.
[0059] Example 5 Preparation of siliconizing agent First, 5 parts by weight of a flaky inorganic mineral and 10 parts by weight of deionized water were mixed, stirred evenly, and allowed to stand for 7 minutes, and then an appropriate amount of deionized water was added to prepare a suspension having a 1wt% content of the flaky inorganic mineral, and then 30 parts by weight of nano-ceramic powder was added to the suspension of the flaky inorganic mineral, and stirred at a speed of 1000 rpm for 10 minutes, and then the obtained mixed solution was filtered, and the powder obtained by filtration was placed in a vacuum oven at 50°C and dried to constant weight, and the obtained mixture was set aside; 10 parts by weight of the modified graphene prepared in the above embodiment 1, 3 parts by weight of a dispersant, and 1 part by weight of a defoaming agent are added to 130 parts by weight of the acrylic polymer emulsion prepared in the above embodiment 2, and after stirring to make the mixture uniform, a mixture of nano-ceramic powder and flaky inorganic minerals is added, and after shearing and dispersion, the siliconization treatment agent is obtained.
[0060] Example 6 Application and use of siliconizing agent: S1, using an alkaline cleaning solution to clean the metal surface: first, using the alkaline cleaning solution to clean the metal surface, then rinsing the alkaline cleaning solution with clean water and drying it; wherein the alkaline cleaning solution includes 5wt% of sodium carbonate, 1wt% of an emulsifier, 10wt% of sodium phosphate and 20wt% of sodium carbonate; S2, roughening the metal surface by high-temperature burning with open flame: the metal parts are placed in an open flame at 600-650°C for high-temperature burning of the entire surface. The area to be roughened is burned by the open flame for a cumulative time of about 3-4 minutes; S3, coating the siliconizing agent: first, place the metal part in a sealed container, and pour the siliconizing agent prepared in Example 3 into it. After the metal part is completely immersed in the siliconizing agent, evacuate the sealed container to a pressure of 10 kPa, and maintain the pressure for 5 minutes. Then, inject air into the sealed container. When the pressure in the sealed container reaches atmospheric pressure, open the sealed container, take out the metal part, and then place the metal part in an oven at 60°C to dry.
[0061] Example 7 Application and use of siliconizing agent: S1, using an alkaline cleaning solution to clean the metal surface: first, using the alkaline cleaning solution to clean the metal surface, then rinsing the alkaline cleaning solution with clean water and drying it; wherein the alkaline cleaning solution includes 5wt% of sodium carbonate, 1wt% of an emulsifier, 10wt% of sodium phosphate and 20wt% of sodium carbonate; S2, roughening the metal surface by high-temperature burning with open flame: the metal parts are placed in an open flame at 680~750℃ for high-temperature burning of the entire surface. The area to be roughened is burned by the open flame for a cumulative time of about 5~6 minutes; S3, coating the siliconizing agent: first, place the metal part in a sealed container, and pour the siliconizing agent prepared in Example 4 into it. After the metal part is completely immersed in the siliconizing agent, evacuate the sealed container to a pressure of 30 kPa, and maintain the pressure for 7 minutes. Then, inject air into the sealed container. When the pressure in the sealed container reaches atmospheric pressure, open the sealed container, take out the metal part, and then place the metal part in an oven at 70°C to dry.
[0062] Example 8 Application and use of siliconizing agent: S1, using an alkaline cleaning solution to clean the metal surface: first, using the alkaline cleaning solution to clean the metal surface, then rinsing the alkaline cleaning solution with clean water and drying it; wherein the alkaline cleaning solution includes 5wt% of sodium carbonate, 1wt% of an emulsifier, 10wt% of sodium phosphate and 20wt% of sodium carbonate; S2, roughening the metal surface by high-temperature burning with open flame: the metal parts are placed in an open flame at 750-800°C for high-temperature burning of the entire surface. The area to be roughened is burned by the open flame for a cumulative time of about 8-9 minutes; S3, coating the siliconizing agent: first, place the metal part in a sealed container, and pour the siliconizing agent prepared in Example 5 into it. After the metal part is completely immersed in the siliconizing agent, evacuate the sealed container to a pressure of 50 kPa, and maintain the pressure for 10 minutes. Then, inject air into the sealed container. When the pressure in the sealed container reaches atmospheric pressure, open the sealed container, take out the metal part, and then place the metal part in an oven at 80°C to dry.
[0063] Comparative Example 1 Application and use of siliconizing agent: The only difference between it and the above-mentioned embodiment 7 is that the preparation process of the modified graphene in the siliconizing agent used therein is: Instead of preparing a silicon dioxide deposition layer on the surface of the graphene microsheets, 8 parts by weight of graphene microsheets are directly dispersed in 10 parts by weight of polydimethylsilicone oil and 3 parts by weight of linear aminosilicone oil. After the graphene microsheets are evenly dispersed by ultrasound, the obtained mixed system is put into a reactor, heated to 350°C under vacuum, kept warm for 2 hours, then cooled to 100°C, and 5 parts by weight of linear hydroxyl silicone oil are added. After reacting for 1 hour under stirring, modified graphene is obtained.
[0064] Comparative Example 2 Application and use of siliconizing agent: The only difference between it and the above-mentioned embodiment 7 is that the preparation process of the modified graphene in the siliconizing agent used therein is: First, 8 parts by weight of graphene microsheets are dispersed in 100 parts by weight of an ethanol aqueous solution, wherein the ethanol content in the ethanol aqueous solution is 40 wt %, then an acid solution is added dropwise to adjust the pH of the mixed solution to 3, and then 2.6 parts by weight of nano-silicon dioxide powder is added. After the addition of the nano-silicon dioxide powder, stirring is continued for 4 hours, and then filtered. The obtained solid powder is calcined at 500° C. for 2 hours under an inert atmosphere to obtain a flaky graphene with silicon dioxide deposited on the surface; The obtained flaky graphene with surface-deposited silicon dioxide is then dispersed in 10 parts by weight of polydimethylsilicone oil and 3 parts by weight of linear aminosilicone oil. After the graphene microsheets are evenly dispersed by ultrasound, the obtained mixed system is put into a reactor, heated to 350°C under vacuum, kept warm for 2 hours, then cooled to 100°C, and 5 parts by weight of linear hydroxyl silicone oil are added. After reacting for 1 hour under stirring, modified graphene is obtained.
[0065] Comparative Example 3 Application and use of siliconizing agent: The only difference between it and the above-mentioned embodiment 7 is that the preparation process of the modified graphene in the siliconizing agent used therein is: First, 8 parts by weight of graphene microsheets are dispersed in 100 parts by weight of an ethanol aqueous solution, wherein the ethanol content in the ethanol aqueous solution is 40 wt%, then an acid solution is added dropwise to adjust the pH of the mixed solution to 3, and then 60 parts by weight of an ethyl orthosilicate solution is slowly added dropwise, wherein the ethyl orthosilicate solution is an ethanol solution with an ethyl orthosilicate content of 15 wt%, and the ethyl orthosilicate solution needs to be added dropwise within 60 minutes; after the ethyl orthosilicate solution is added dropwise, stirring is continued for 4 hours, and then filtered, and the obtained solid powder is calcined at 500° C. for 2 hours under the protection of an inert atmosphere to obtain a flaky graphene with silicon dioxide deposited on the surface; The obtained flaky graphene with surface-deposited silicon dioxide is then dispersed in 10 parts by weight of polydimethylsilicone oil and 3 parts by weight of linear aminosilicone oil. After the graphene microsheets are evenly dispersed by ultrasound, the obtained mixed system is put into a reactor, heated to 350°C under vacuum, kept warm for 2 hours, and then cooled to room temperature to obtain modified graphene.
[0066] Comparative Example 4 Application and use of siliconizing agent: The only difference between it and the above-mentioned embodiment 7 is that the preparation process of the modified graphene in the siliconizing agent used therein is: First, 8 parts by weight of graphene microsheets are dispersed in 100 parts by weight of an ethanol aqueous solution, wherein the ethanol content in the ethanol aqueous solution is 40wt%, and then an acid solution is added dropwise to adjust the pH of the mixed solution to 3, and then 60 parts by weight of an ethyl orthosilicate solution is slowly added dropwise, wherein the ethyl orthosilicate solution is an ethanol solution with an ethyl orthosilicate content of 15wt%, and the ethyl orthosilicate solution needs to be added dropwise within 60 minutes; after the ethyl orthosilicate solution is added dropwise, the reaction is continued with stirring for 4 hours, and then filtered, and the obtained solid powder is calcined at 500°C for 2 hours under the protection of an inert atmosphere to obtain flaky graphene with silicon dioxide deposited on the surface, which is used as a modified graphene to prepare a silicification treatment agent.
[0067] Comparative Example 5 Application and use of siliconizing agent: The only difference between it and the above-mentioned Example 7 is that during the preparation process of the acrylic ester polymer emulsion in the siliconizing agent used therein: no pentaerythritol triacrylate is added, and the rest are the same.
[0068] Comparative Example 6 Application and use of siliconizing agent: The only difference between it and the above-mentioned Example 7 is that during the preparation process of the siliconizing agent used therein, the flaky inorganic mineral is directly dispersed in deionized water to prepare a suspension with a flaky inorganic mineral content of 3 wt %, and the rest are the same.
[0069] Comparative Example 7 Application and use of siliconizing agent: The only difference between it and the above-mentioned embodiment 7 is that after the metal surface is cleaned with an alkaline cleaning solution, the metal surface is not roughened by high-temperature burning with an open flame according to the process described in step S2, but is directly coated with a siliconizing agent.
[0070] Performance Test: Preparation of test samples: The metal parts coated with siliconizing agent prepared in Examples 6 to 8 and Comparative Examples 1 to 7 were coated with TGIC-pure polyester powder paint, and the curing conditions were 150°C and 20 minutes. The thickness of the cured paint film was 100-120 um.
[0071] Then, the obtained samples were tested as follows, and the test results are shown in Table 1 below: (1) Corrosion resistance test: The surface of the painted metal part is scratched and then subjected to a neutral salt spray test according to ASTM B 117. The tested samples are then rated according to ASTM D1654. Table 1 shows the evaluation level corresponding to the single-side peeling distance specified in ASTM D1654. Level 0 is the worst and level 10 is the best.
[0072] (2) Adhesion test: The 100-grid method is used for testing. After drawing 100 grids, 3M 600 high-grade transparent tape is used to stick them once to test the adhesion of the paint film on the substrate. If there is no shedding, it is excellent; if there is shedding of less than 10 grids, it is good; if there is shedding of 10 to 20 grids, it is medium; and if there is shedding of more than 20 grids, it is poor.
[0073] (3) Impact resistance test: 49N / cm 2 After the impact test with a force of , observe whether there are radial cracks on the surface of the sample.
[0074] Table 1 Performance test results Corrosion resistance level Adhesion level (number of falling grids) Impact resistance test Example 6 8 Excellent (0) No radioactive cracks Example 7 8 Excellent (0) No radioactive cracks Example 8 8 Excellent (0) No radioactive cracks Comparative Example 1 6 Good (6) No radioactive cracks Comparative Example 2 7 Good (3) No radioactive cracks Comparative Example 3 7 Good (7) No radioactive cracks Comparative Example 4 6 Medium (11) Slight radioactive cracks appeared Comparative Example 5 7 Good (4) No radioactive cracks Comparative Example 6 7 Excellent (0) No radioactive cracks Comparative Example 7 6 Medium (17) Slight radioactive cracks appeared The embodiments of the present application are described above in conjunction with the accompanying drawings. In the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. The present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.
Claims
1. A method for preparing a siliconizing agent, characterized in that: The siliconizing agent comprises the following raw materials in parts by weight: 5-10 parts of modified graphene; 3-5 parts of flaky inorganic minerals; 15-30 parts of nano ceramic powder; 80-130 parts of acrylic polymer emulsion; Dispersant 0.5~3 parts; Defoaming agent 0.3~1 part.
2. The method for preparing a siliconizing agent according to claim 1, characterized in that: The preparation process of the modified graphene is as follows: First, 5 to 10 parts by weight of graphene microsheets are dispersed in 80 to 150 parts by weight of an ethanol aqueous solution, wherein the ethanol content in the ethanol aqueous solution is 40 to 50 wt%, then an acid solution is added dropwise to adjust the pH of the mixed solution to 2.5 to 4, and then 50 to 70 parts by weight of an ethyl orthosilicate solution is slowly added dropwise, wherein the ethyl orthosilicate solution is an ethanol solution with an ethyl orthosilicate content of 10 to 20 wt%; after the ethyl orthosilicate solution is added dropwise, the reaction is continued with stirring for 3 to 5 hours, and then filtered, and the obtained solid powder is calcined at 500 to 600° C. for 1 to 2 hours under the protection of an inert atmosphere to obtain a flaky graphene with silicon dioxide deposited on the surface; The obtained flaky graphene with surface-deposited silicon dioxide is then dispersed in 5-10 parts by weight of polydimethylsilicone oil and 3-5 parts by weight of linear aminosilicone oil. After the graphene microsheets are evenly dispersed by ultrasound, the obtained mixed system is put into a reactor, the temperature is raised to 300-400° C. under vacuum, and the temperature is kept for reaction for 2-3 hours, then the temperature is lowered to 80-120° C., 3-5 parts by weight of linear hydroxyl silicone oil are added, and the reaction is carried out for 1-2 hours under stirring to obtain modified graphene.
3. The method for preparing a siliconizing agent according to claim 1, characterized in that: The flaky inorganic mineral is selected from one or more of mica, kaolin, talc, montmorillonite, chlorite, and pyrophyllite. The average thickness of the flaky inorganic mineral is ≤1 um, and the particle size is ≤10 um.
4. The method for preparing a siliconizing agent according to claim 1, characterized in that: The monomers forming the acrylic ester polymer include 40 to 60 parts by weight of methyl methacrylate, 15 to 20 parts by weight of n-butyl acrylate, 5 to 10 parts by weight of pentaerythritol triacrylate, and 5 to 10 parts by weight of ethyl acrylate.
5. The method for preparing a siliconizing agent according to claim 4, characterized in that: The preparation process of the acrylic polymer emulsion is as follows: First, an emulsifier is added to deionized water to prepare a solution 1 with an emulsifier content of 3-5wt%, and potassium persulfate is added to deionized water to prepare a solution 2 with a potassium persulfate content of 0.5-3wt%. Then, methyl methacrylate, n-butyl acrylate, pentaerythritol triacrylate and ethyl acrylate are added to the solution 1, and after stirring evenly, the obtained mixed solution is heated to 70-80°C, and the solution 2 is added, and then the reaction is stirred at 70-80°C for 1-2h, and then a photoinitiator is added, and after stirring to make the mixture evenly mixed, the acrylic ester polymer emulsion is obtained.
6. The method for preparing a siliconizing agent according to claim 5, characterized in that: In the preparation process of the acrylic polymer emulsion, the weight ratio of the added amounts of the monomer, emulsifier and photoinitiator forming the acrylic polymer is (100-150): (3-8): (1-5).
7. The method for preparing a siliconizing agent according to claim 1, characterized in that: The preparation method of the siliconizing agent comprises: First, 3 to 5 parts by weight of a flaky inorganic mineral and 5 to 10 parts by weight of deionized water are mixed, stirred evenly, and allowed to stand for 5 to 10 minutes, and then an appropriate amount of deionized water is added to prepare a suspension having a flaky inorganic mineral content of 1 to 3 wt%, and then 15 to 30 parts by weight of a nano-ceramic powder is added to the suspension of the flaky inorganic mineral, and stirred at a speed of 300 to 1000 rpm for 5 to 10 minutes, and then the obtained mixed solution is filtered, and the powder obtained by filtration is placed in a vacuum oven at 30 to 50° C. and dried to constant weight, and the obtained mixture is set aside; The modified graphene, dispersant and defoamer in the formula amount are added to the acrylic polymer emulsion, stirred to make the mixture uniform, and then a mixture of nano-ceramic powder and flaky inorganic minerals is added, and after shearing and dispersion, the siliconization treatment agent is obtained.
8. A method for using a siliconizing agent, characterized in that: The method for using the siliconizing agent is used for the siliconizing agent according to any one of claims 1 to 7, and the method for using the siliconizing agent comprises the steps of: S1, using alkaline cleaning liquid to clean the metal surface; S2, roughening the metal surface by high temperature burning with open flame; S3, applying the siliconizing agent.
9. The method for using a siliconizing agent according to claim 8, characterized in that: The step S2 comprises: placing the metal component in an open flame at 600-800° C. for high-temperature burning, and the high-temperature burning treatment time is 3-10 minutes.
10. The method for using a siliconizing agent according to claim 8, characterized in that: In step S3, the process of applying the siliconizing agent is as follows: First, place the metal parts in a sealed container and fill it with the siliconizing agent. After the metal parts are completely immersed in the siliconizing agent, evacuate the sealed container to a pressure of 10-50 kPa and maintain the pressure for 5-10 minutes. Then, inject air into the sealed container. When the pressure in the sealed container reaches atmospheric pressure, open the sealed container, take out the metal parts, and then place the metal parts in an oven at 60-80°C for drying.
Citation Information
Patent Citations
Novel nano coating and preparation method thereof
CN116144222A
Heat treatment device and treatment method
KR1020210011347A
Graphene oxide-tetraethyl orthosilicate / silane composite gel material, and preparation method and use thereof
US20220396705A1
Multifunctional repellent materials
WO2014012079A1